2014
DOI: 10.1007/s10753-014-9932-z
|View full text |Cite
|
Sign up to set email alerts
|

Wogonoside Ameliorates Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: Wogonoside has been reported to have anti-inflammatory properties. In this study, we evaluated the effect of wogonoside on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. Male BALB/c mice with ALI, induced by intranasal instillation of LPS, were treated with wogonoside 1 h prior to LPS exposure. Mice treated with LPS alone showed significantly increased TNF-α, IL-6, and IL-1β levels in the bronchoalveolar lavage fluid (BALF). When pretreated with wogonoside, the TNF-α, IL-6, and IL-1β levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In addition, histopathological study also indicated that PLD treatment markedly attenuated the neutrophil infiltration in the lungs. LPS is known to induce the production of several inflammatory and chemotactic cytokines [27]. TNF-α and IL-6 are characterized cytokines involved in the inflammatory process of ALI [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, histopathological study also indicated that PLD treatment markedly attenuated the neutrophil infiltration in the lungs. LPS is known to induce the production of several inflammatory and chemotactic cytokines [27]. TNF-α and IL-6 are characterized cytokines involved in the inflammatory process of ALI [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we will study the MAPK signaling pathway. The NF-κB signaling pathway plays an important role in the regulation of the inflammatory and immune responses, inducing the transcription of a series of genes encoding cytokines and chemokines [32]. Under normal conditions, NF-κB is associated with its inhibitor IκB-α in the cytoplasm [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was demonstrated that treatment with 25 or 50 mg/kg of wogonoside significantly inhibited inflammation through the suppression of NF-κB/IκB in an SCI rat model. Similarly, Zhang et al (7) reported that wogonoside ameliorates LPS-induced acute lung injury in mice through the suppression of TLR4-mediated NF-κB signaling. The NLRP3 inflammasome promotes the secretion of IL-1β, IL-18 and IL-33, and the production of these factors is critical in the control of pathological infection (24).…”
Section: Discussionmentioning
confidence: 90%
“…1) has been reported to possess extensive pharmacological activities. In addition to anti-inflammatory, anti-allergy, anti-viral and antipyretic properties, recent studies have demonstrated that wogonoside possesses anti-oxidative and anti-tumor effects, along with cardiovascular protective effects (7,8). Wogonoside is derived from Scutellaria baicalensis, and has exhibited efficacy as an antithrombotic, antihypertensive and antitumor therapeutic, and in the treatment of coronary heart disease (9).…”
Section: Introductionmentioning
confidence: 99%